THE USE OF BINJAI CITY CIRCULATION LIBRARIES IN INCREASING STUDENTS' INTEREST IN READING AT MIS MIFTAHUL KHAIR EDUCATIONAL FOUNDATION SCHOOLS - Ritonga, Husin Syawali; Ramadhan, All Rizky (PERSPEKTIF: Journal of Social and Library Science, 2023)
This study aims to find out the use of mobile libraries at MIS Miftahul Khair, to find out the programs implemented by the mobile library managers in the city of Binjai in the use of mobile libraries for the reading interest of MIS Miftahul Khair students, to find out the constraints that exist in the use of mobile libraries on the city of Binjai. This type of research is a qualitative research with a descriptive approach. The techniques used in data collection are interviews, observation, and documentation. While the data analysis technique goes through three stages, namely, data reduction, data presentation and drawing conclusions. The results of this study indicate that the management of the use of mobile libraries to entrust book collections at MIS Miftahul Khair has gone well, both in terms of planning, organizing, actuating, monitoring, and evaluating. As well as programs that have been implemented on the part of the school can increase students' interest in reading at MIS Miftahul Khair. And the constraints of the library around the city of Binjai include collections with the same title, there are still not many of them, the borrowing time limit is still minimal, and the implementation program is still not optimal.